Performance Analysis of Test Path Generation Techniques Based on Complex Activity Diagrams - Sornkliang, Walaiporn; Phetkaew, Thimaporn (Informatica, 2021)
Effort reduction in software testing is important to reduce the total cost of the software development project. UML activity diagram is used by the tester for test path generation. It is hard to select the appropriate test path generation technique to diminish the effort of software testing. In the experiment, we compared the efficiency of 11 commonly-used test path generation techniques with both simple activity diagrams and the constructed complex activity diagrams. The experimental results summarized in three aspects. 1) For all possible path testing, the Activity Convert Grammar was the most appropriate test path generation technique, which can generate the number of paths equivalent to the target number of all possible paths. 2) Testing all possible paths for the large or complex object-oriented method is laborious. Almost all techniques could generate test paths that cover basis path coverage. 3) To compare the efficiency of test path generation algorithms, the percentage test path deviation to the target number of all possible paths of the Activity Convert Grammar was 0% for both a Complex Concurrent Structure activity diagram and a Complex Control Structure activity diagram. We also suggested the suitable UML activity diagram for each test path generation method.